Variation in behavioral preference and calcium binding expression in two Synodontis catfishes with different communication modalities - Carlos Daniel Corrales Parada; Iva Udovičić; Giulia Haschei; Boris Philippe Chagnaud (Frontiers in Neuroanatomy)
Animals use different communication modalities for social interactions, often showing sensory adaptations linked to their preferred signaling system. How such adaptations affect individual processing centers usually remains elusive due to interspecies differences. One system in which such adaptations can be investigated are Synodontis catfish. Synodontids generally use acoustic signals for social communication, but in some species, they generate electric signals. This allows to investigate adaptations of networks associated with social signal detection in closely related species. We investigated potential sensory adaptations in two Synodontis species (Synodontis grandiops - SG and Synodontis nigriventris - SN) with different communication channels. We tested their behavioral preferences toward different sensory modalities and found strong preferences for conspecifics. To investigate potential adaptations at the cellular level, we focused on the torus semicircularis (TS), a major midbrain sensory hub for auditory and electric sensory processing. We found an increase in projections from the anterior tuberal nucleus (AT) to the lateral TS (TSl, which processes electrosensory information) in SN, but no difference in the projections from the central TS (TSc) to AT in either species. An enhanced density of calcium binding proteins in the TSl was found only in SN. As electrocommunication is a derived communication channel in Synodontis, our findings suggest that a shift to electric communication may have led to (i) stronger projections to and from sensory regions, and (ii) a change in neurochemical profile, which together might facilitate social signal detection.